Seismic vulnerability and parametric study on a bare frame building in Nepal - R. Dumaru (2016)
The influence of the infill masonry walls in the structural response of reinforced concrete (RC) structures when subjected to earthquakes is not considered in Nepal National Building code and Indian Standard code. Field observations carried out after the 25th April Gorkha earthquake in Nepal reinforce the importance of the infill walls, namely, through the significant increasing of the structural stiffness and by the possibility of introducing unexpected mechanisms that can cause extensive damages or even the collapse of the structure. This article focuses on the study of an existing bare frame, representative of the Nepalese RC buildings, which was modeled and calibrated with data results collected from ambient vibration tests. Initially, a parametric study was conducted with the aim of evaluating the influence of parameters, such as concrete strength and elasticity modulus, slab thickness, and columns cross section in the natural frequencies of the building. The influence of the infill masonry walls in the structural response was evaluated through the modeling of three different numerical models with different disposition of the infill panels from the calibrated existing structure. The seismic vulnerability assessment was performed through non-linear static pushover and dynamic analysis. The results will be presented and discussed in terms of base maximum inter-storey drifts and maximum base shear.